أثر استخدام لعض استراتيجيات التعلم النشط في تحصيل طلبة الصف الخامس الا حياتي في مادة علم الاحياتي في مادة علم الأحياء وميولهم العلمية - حسن، أحمد عبيد; سلمان، بتول جيجان (جامعة القادسية - كلية التربية, 2022)
هدف هذا البحث التعرف على أثر استخدام بعض استراتيجيات التعلم النشط في تحصيل طلبة الخامس الأحيائي في مادة علم الأحياء وميولهم العلمية ولأجل التحقق من هدف هذا البحث قام الباحثان بوضع فرضيات صفرية وكي يتم التأكد من هذه الفرضيات الصفرية أجرت تجربة وفق المنهج التجريبي ذا الضبط الجزئي والاختبار البعدي لمجموعتين متكافئتين هما مجموعتي البحث لتحصيل مادة الأحياء والميول العلمية تمثلت عينة البحث بطلاب الصف الخامس الأحيائي في ثانوية كلية بغداد موزعة على ثلاثة شعب شملت (33، 33، 32) طالب إحداهما مثلت مجموعة تجريبية أولى والتي درست وفق استراتيجية الأنشطة المتدرجة والأخرى مجموعة تجريبية ثانية درست وفق استراتيجية الكرسي الساخن والثالثة مثلت مجموعة ضابطة وقد تم إجراء التكافؤ في المتغيرات الأتية (التحصيل الدراسي للعام السابق والعمر الزمني والميول العلمية)، وقد قام الباحثان بأعداد أداتين للبحث هما اختبار تحصيلي نوعه الاختيار من متعدد متكون من ‎(40) فقرة واختبار الميول العلمية نوع الاختبار أيضا الاختيار من متعدد وتكون من (25) فقرة‏ وتم التأكد من الخصائص السايكومترية للأداتين، وطبقت التجربة في الفصل الدراسي الأول قام الباحثان بتدريس مجموعتي البحث بنفسها وبعد الانتهاء من التجربة قام الباحثان بالتحليل الإحصائي باستخدام اختبار تائي (t - test) للعينتين المستقلتين وأظهرت النتائج تفوق طلاب المجموعة التجريبية الأولى والثانية على طلاب المجموعة الضابطة في كل من اختبار التحصيل والميول العلمية ولم يظهر فرق بين المجموعتين التجريبية الأولى والثانية في التحصيل بينما وجد فرق بينهما في نتائج اختبار الميول العلمية ولصالح مجموعة البحث التجريبية الأولى وحسب نتائج هذا البحث فقد وضعت الباحثة عدد من الاستنتاجات وعدد من التوصيات المتعلقة بنتائج البحث كما وضعت عددا من المقترحات. The aim of this research is to identify the effect of using some active learning strategies on the achievement of students of the fifth biological in the subject of biology and their scientific tendencies. In order to verify the goal of this research, the two researchers developed null hypotheses and in order to verify these null hypotheses, an experiment was conducted according to the experimental method of partial control and post-test For two equal groups, they are the two research groups for the achievement of biology and scientific tendencies the research sample was represented by fifth-grade students of biology in Baghdad College High School distributed into three divisions that included (33, 33, 32) students, one of which represented a first experimental group that studied according to the strategy of gradual activities and the other a second experimental group that studied according to the strategy of the hot chair and the third represented a control group. Conduct parity in the following variables (academic achievement of the previous year, chronological age and scientific tendencies) The two researchers have prepared two tools for the research, namely, an achievement test of its kind, multiple choice, consisting of (40) items, and a test for scientific tendencies. The type of test is also multiple choice, consisting of (25) items, and the psychometric properties of the two tools were verified. The experiment was applied in the first semester, the two researchers taught the two research groups on their own, and after completing the experiment, the researcher conducted a statistical analysis using a t-test for the two independent samples, and the results showed that the students of the first and second experimental group outperformed the control group students in both the achievement test and scientific tendencies there was no difference between the first and second experimental groups in achievement, while a difference was found between them in the results of the scientific tendency test and for the benefit of the first experimental research group according to the results of this research, the researchers drew up a number of conclusions and recommendations related to the results of the research, as well as a number of proposals.
Keywords: التعلم النشط -- الاستراتيجيات التدريسية -- الميول العلمية -- الإفادة العلمية